Comparative characteristics of the endogenous synthesis of carcinogenic nitrosamines depending on the design of the experiment (Environment & Health, 2017)
Objective. We determined the peculiarities of the endogenous synthesis of carcinogenic nitrosamines (NA) depending on the conditions of the experiment according to the data of our own research.Materials and methods. The studies were carried out on white outbred rats in 3 series of the experiments with different doses (concentrations) used for the administration of precursors of nitrosamine synthesis (PNA), routes, duration of administration and duration of the experiments. Doses of PNA were chosen taking into account their real levels in the environment. The level of endogenously synthesized HA (ENA) — nitrosodimethylamine and nitrosodiethylamine in the organs of the experimental animals was determined by the gas chromatography method. The risk of HA was assessed by the indicators of tumor development (frequency, malignancy, morphogenesis, localization, latent period, etc.) established in pathomorphological studies. The obtained digital data were processed by the methods accepted in biomedical studies using the Student's test and also Pirson's χ2.Results. In all experiments at the introduction of the complexes of different PNA the presence of ENA in the organs (liver, kidneys, lungs) was noted in 7 hours after the start of the PNA administration. Their number in the organs increased to a certain level and then was approximately the same despite the continuation of the PNA introduction. After the termination of the PNA administration the ENA were not detected in the organs. In chronic experiments, a dose-dependent development of tumors of different organs was noted. Nitrogen dioxide played a decisive nitrosating role in the experiment with the introduction of nitrogen oxides (inhalation), sodium nitrite in a complex with amidopirin (orally). In comparison with this experiment, in the experiments where the animals were orally administrated tetracycline with sodium nitrite, the intensity of endogenous synthesis and the content of ENA in the organs were lower, they were not determined in the lungs.Conclusions. Endogenous synthesis of HA was proved in the experiment on white outbred rats, HA level and intensity of the formation depended on chemical structure, dose and pathways of the precursors of their synthesis. There was no material cumulation of carcinogens in organs at the simultaneous accumulation of functional-and-structural changes in the organism leading to the development of tumors. Frequency, morphology, genesis, and localization of induced tumors were proved to be determined by the toxico-pharmacological features of the precursors and the number of endogenously synthesized nitrosamines.
Keywords: nitrosodimethylamine; nitrosodiethylamine; endogenous synthesis; precursors of synthesis; carcinogenic effect